2015
DOI: 10.1155/2015/809289
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Based Methods of Liver Fibrosis Assessment in Viral Hepatitis: A Practical Approach

Abstract: Liver fibrosis represents the repair mechanism in liver injury and is a feature of most chronic liver diseases. The degree of liver fibrosis in chronic viral hepatitis infections has major clinical implications and presence of advanced fibrosis or cirrhosis determines prognosis. Treatment initiation for viral hepatitis is indicated in most cases of advanced liver fibrosis and diagnosis of cirrhosis entails hepatology evaluation for specialized clinical care. Liver biopsy is an invasive technique and has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…At present, serological indexes are the main clinical methods to assess hepatic fibrosis, although the accuracy needs to be improved[ 9 - 11 ]. The latest research has shown that ultrasound elastography can measure the hardness of liver tissue to determine the degree of hepatic fibrosis with features of non-invasiveness, simplicity, speed and repeatability[ 12 , 13 ]. However, its diagnostic accuracy is not high, and the accuracy of different studies are different[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, serological indexes are the main clinical methods to assess hepatic fibrosis, although the accuracy needs to be improved[ 9 - 11 ]. The latest research has shown that ultrasound elastography can measure the hardness of liver tissue to determine the degree of hepatic fibrosis with features of non-invasiveness, simplicity, speed and repeatability[ 12 , 13 ]. However, its diagnostic accuracy is not high, and the accuracy of different studies are different[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%